BIOSPHERE – THE PHENOMENON OF GEOLOGICAL NATURE - Kravchuk, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article briefly analysis the evolution of the idea of the biosphere, its philosophical unterpretation, perceptions and the prospects for the biosphere transition into the noosphere.